2020
DOI: 10.3390/nu12123693
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Modified Mediterranean Diet Score (mMDS) with Anthropometric and Biochemical Indices in US Career Firefighters

Abstract: The Mediterranean diet is associated with multiple health benefits, and the modified Mediterranean Diet Score (mMDS) has been previously validated as a measure of Mediterranean diet adherence. The aim of this study was to examine associations between the mMDS and anthropometric indices, blood pressure, and biochemical parameters in a sample of career firefighters. The participants were from Indiana Fire Departments, taking part in the “Feeding America’s Bravest” study, a cluster-randomized controlled trial tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 65 publications
3
16
0
Order By: Relevance
“…The authors reported the beneficial effects of a higher MD adherence on both HDL-c and TG levels, the latter coinciding with more frequent olive oil intake, the main denominator of the MD. Results on HDL-c were in agreement with a cross-sectional study [ 7 ] and an intervention study [ 6 ] on healthy volunteers also included in the issue [ 6 ], and results on HDL-c and TG are in agreement with the systematic review published on metabolic syndrome specific risk factors [ 1 ]. The authors found that nutritional counselling improved adherence, as was also suggested by Grabia and colleagues in their study on T1DM women [ 2 ].…”
supporting
confidence: 87%
See 3 more Smart Citations
“…The authors reported the beneficial effects of a higher MD adherence on both HDL-c and TG levels, the latter coinciding with more frequent olive oil intake, the main denominator of the MD. Results on HDL-c were in agreement with a cross-sectional study [ 7 ] and an intervention study [ 6 ] on healthy volunteers also included in the issue [ 6 ], and results on HDL-c and TG are in agreement with the systematic review published on metabolic syndrome specific risk factors [ 1 ]. The authors found that nutritional counselling improved adherence, as was also suggested by Grabia and colleagues in their study on T1DM women [ 2 ].…”
supporting
confidence: 87%
“…This SI contains multifaceted research articles and a systematic review, which have addressed these issues both in healthy individuals and in those with specifically defined disease states or risk factors. Specifically, this SI contains research that has been carried out in not only the general population, but also among patients with Type 1 diabetes mellitus (T1DM) [ 2 ] or dyslipidemia [ 3 , 4 , 5 ], as well as among firefighters who are proxy to healthy and physically fit individuals [ 6 , 7 ], adding valuable information to the pre-stated gap in knowledge.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The choice of the recipe composition of the instant granular drink was carried out taking into account the content of ingredients that enhance the positive effect on each other and on the body as a whole from the point of view of the prevention of vitamin deficiency in firefighters-rescuers. So, having carried out a number of studies and guided by literature data, the best composition of the drink is as follows: modified potato starch, powdered sugar, concentrated chokeberry juice, black chokeberry cake, thickened curd whey, native curd whey, citric acid [8][9].…”
Section: Resultsmentioning
confidence: 99%